1975
DOI: 10.1021/jm00235a010
|View full text |Cite
|
Sign up to set email alerts
|

Aminobenzoic acid diuretics. 7. 3-Substituted 4-phenyl-, 4-arylcarbonyl-, and 4-arylmethyl-5-sulfamoylbenzoic acids and related compounds

Abstract: Various 4-substituted 3-alkylamino-, 3-alkoxy-, 3-alkylthio-, and 3-alkyl-5-sulfamoylbenzoic acids related to known aminobenzoic acid diuretics were synthesized and screened for their diuretic properties in dogs. The tabulated results from a 3-hr test period revealed that generally the diuretic profile and potency could be retained when 3-alkoxy, 3-alkylthio, and 3-phenethyl were substituted for the 3-alkylamino moiety. The high potency of several 3-alkoxy-, 3-alkylthio-, and 3-phenethyl-4-benzoyl-5-sulfamoylb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1975
1975
2003
2003

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…BSTBA is a bumetanide analog, which is a potent loop diuretic (66), and contains a photoreactive benzophenone group. We have used [3Hj4-benzoyl-5-sulfamoyl-3-(3thenyloxy) benzoic acid ([3HjBSTBA) to photo label membranes from dog kidney, duck red cells, and shark rectal gland (24, 39-4 1).…”
Section: Structure Of the (Na-k-cl) Cotransportermentioning
confidence: 99%
“…BSTBA is a bumetanide analog, which is a potent loop diuretic (66), and contains a photoreactive benzophenone group. We have used [3Hj4-benzoyl-5-sulfamoyl-3-(3thenyloxy) benzoic acid ([3HjBSTBA) to photo label membranes from dog kidney, duck red cells, and shark rectal gland (24, 39-4 1).…”
Section: Structure Of the (Na-k-cl) Cotransportermentioning
confidence: 99%
“…This result suggests that I1 has an E configuration with regard to the N=N double bond. Using the method of Nielsen et al (1975), this compound was easily obtained in nearly quantitative yield by reduction of N -b -nitrobenzoy1)-L-glutamic acid.…”
Section: Resultsmentioning
confidence: 99%
“…This analogue of bumetanide, described by Nielsen et al (1975), has potent diuretic activity. Haas and Forbush (1987) showed that BSTBA competes with [3H]-bumetanide in reversible binding and that BSTBA itself binds reversibly with high affinity to the membranes.…”
Section: Discussionmentioning
confidence: 99%